Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/aem.06923-11
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond Formation and Activation of Escherichia coli β-Galactosidase under Oxidizing Conditions

Abstract: ABSTRACTEscherichia coliβ-galactosidase is probably the most widely used reporter enzyme in molecular biology, cell biology, and biotechnology because of the easy detection of its activity. Its large size and tetrameric structure make this bacterial protein an interesting model for crystallographic studies and atomic mapping. In the present study, we investigate a version of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It cannot be excluded that these cysteines may become oxidized in cytosol of E. coli . Although disulfide bonds are rarely formed in E. coli cytoplasmic proteins, exceptions to this general rule do exist (Aslund et al, 1999; Jakob et al, 1999; Seras-Franzoso et al, 2012). Our NMR analysis of U, H-P1 and H-P2 revealed chemical shift differences in particular for the six cysteine residues at positions 15, 18, 22, 32, 41, and 78 (in NTD) (Figure 2C; inset and Table 1), both in 1D spectra (Figure 2D) and in 2D- 1 H- 15 N correlated experiments (Figure 2E and 2F).…”
Section: Resultsmentioning
confidence: 99%
“…It cannot be excluded that these cysteines may become oxidized in cytosol of E. coli . Although disulfide bonds are rarely formed in E. coli cytoplasmic proteins, exceptions to this general rule do exist (Aslund et al, 1999; Jakob et al, 1999; Seras-Franzoso et al, 2012). Our NMR analysis of U, H-P1 and H-P2 revealed chemical shift differences in particular for the six cysteine residues at positions 15, 18, 22, 32, 41, and 78 (in NTD) (Figure 2C; inset and Table 1), both in 1D spectra (Figure 2D) and in 2D- 1 H- 15 N correlated experiments (Figure 2E and 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Correct formation of disulfide bonds on an unfolded protein followed by the correct folding of the protein is catalyzed in the periplasm by the Dsb machinery (Berkmen, ). Thus, the higher free thiol content of SP TorA :: hm CA is indicative of a higher fraction of (partially) misfolded enzymes, resulting in lower specific activity (Seras‐Franzoso et al, ). In addition, the purified SP PelB :: hm CA showed a higher thermal stability with a half‐life of 7.6 hr compared with that of SP TorA :: hm CA with a half‐life of 5.6 hr at 60°C (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that this lack of activity was due to the presence of the glutathione system in Gram-negative bacteria which helps to mediate resistance to auranofin in these pathogens 13 . However, when we assessed auranofin’s antibacterial activity against both wild-type and Origami-2 ( trxb / gor double mutant) E. coli mutant strains, neither strain was susceptible to auranofin even at a concentration of 16 μg/ml 40 . This suggests an alternative mechanism may be responsible for the lack of activity observed with auranofin against Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%